2014
DOI: 10.1152/ajpheart.00043.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of export of anoxia/reoxygenation injury from ischemic to nonischemic cardiomyocytes via inhibition of endocytosis

Abstract: Myocardial infarct size is determined by the death of nonischemic border zone cardiomyocytes caused by export of injury signals from the infarct zone. The countermeasures to limit infarct size, therefore, should be aimed at nonselective blockade of most, if not all, injury signals from entering nonischemic cells. To test whether inhibition of endocytosis might limit infarct size, HL-1 cardiomyocytes were subjected to anoxia (6 h) and reoxygenation (1 h). Anoxic and reoxygenated cells showed a multifold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In the current study, the efficacy of prazosin against anoxia-reoxygenation injury in a mouse model was investigated. The results demonstrated that prazosin decreases the plasma concentration of inflammatory factors, and improves oxidative stress in myocardial cells ( 26 ). Notably, it was observed that prazosin treatment exerts significant anti-apoptotic effects in myocardial cells of mice models of anoxia-reoxygenation injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the efficacy of prazosin against anoxia-reoxygenation injury in a mouse model was investigated. The results demonstrated that prazosin decreases the plasma concentration of inflammatory factors, and improves oxidative stress in myocardial cells ( 26 ). Notably, it was observed that prazosin treatment exerts significant anti-apoptotic effects in myocardial cells of mice models of anoxia-reoxygenation injury.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 mM concentration applied in hearts is thus considered to be relatively selective for dynamin/DRP-1 inhibition. Higher concentrations are employed to inhibit endocytosis, which may participate in either cardiac injury ( Khaidakov et al, 2014;Yang et al, 2016) or protection (Most et al, 2003). Yang et al (2016) found, for example, that 80 mM dynasore reduced internalization of cardioprotective ATPsensitive potassium channels and infarct development during myocardial I-R.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is evidenced that the cellular rate of nutrient or ion uptake (e.g., glucose, Fe 3+ , and K + ) or efflux (e.g., Na + ) is governed by a complement of membrane transporters and receptors that show dynamic localization at both the plasma membrane and the defined intracellular membrane compartments [ 18 ]. Some research showed that endocytosis was upregulated in border zone cardiomyocytes, and inhibition of endocytosis might be an effective approach to prevent export of injury signals from the myocardial infarct size [ 19 ]. In considering endocytosis as the most obvious upregulated pathway in QDB, we speculate that endocytosis process consumes excessive the above mentioned nutrients so that the body appears a series of energy deficiency signs, as so-called Qi-deficiency.…”
Section: Discussionmentioning
confidence: 99%